You will never be me - Sutanto, Jesse Q. (Berkley, 2024)
"When cracks start forming in an influencer's curated life, she finds out that jealousy is just as viral as a video in this riveting suspense novel by bestselling author Jesse Q. Sutanto. Influencer Meredith Lee didn't teach Aspen Palmer how to blossom on social media just to be ditched as soon as Aspen became big. So can anyone really blame Mer for doing a little stalking? Nothing serious, more like Stalking Lite. Then, Mer gets lucky; she finds one of Aspen's kids' iPads and swipes it. Now, she has access to everything: the family calendar and Aspen's social media accounts. Would anyone else be able to resist tweaking things a little here and there, showing up in Aspen's place for meetings with potential sponsors? Mer's only taking back what she deserves--what should have been hers. Meanwhile, Aspen doesn't understand why her perfectly filtered life is falling apart. Sponsors are dropping her, fellow influencers are ghosting her, and even her own husband seems to find her repulsive. If she doesn't find out who's behind everything, she might just lose it all. What everyone seems to forget is that Aspen didn't become one of TikTok's biggest momfluencers by being naive. When Meredith suddenly goes missing, Aspen's world is upended and mysterious threats begin to arrive--but she won't let anything get in the way of her perfect life again"--